PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN MAHASISWA PENGGUNA SMARTPHONE OPPO - Nur, Irawati; Dinsar, Arfandy (Universitas Muhammadiyah Parepare, 2021)
This study aims to examine the effect of the price and product quality partially and simultaneously on student satisfaction using OPPO smartphones. The analysis method used is validity test, reliability test, multiple linear regression, partial test, simultaneous test, determination test (R-square). The data collection method used is by using a questionnaire that has been distributed to respondents. The population in this study was all STIE Amsir Parepare students who use OPPO smartphones. As for the research sample using the Tabachinik and Fidel sample technique, namely by multiplying the number of independent variables by 10-25. For the number of samples to be more proportional, the number of samples taken is 50 samples of students using OPPO brand smartphones. The results of the study show that price and product quality have a joint and significant influence on student satisfaction using the OPPO brand smartphone.